Identification and Detection of Missing RFID Tags using RUN Protocol (International Journal of Engineering and Computer Science, 2018)
As human race or human society is growing, the wildlife/domestic animals are in danger. But as per natures rule, every living creature on this earth is important and has important role in ecosystem. The animals get misplaced sometimes and finding them is a tedious task. RFID and sensors have been deployed to detect and identify missing animals by affixing them with cheap passive RFID tag and monitoring them with RFID readers. In our project, system will help us to detect and find the missing animals using RUN protocol, using this the missing animals will get detected and the location will get generated automatically through google maps. RUN protocol uses slotted aloha for communication between tags and readers. It executes multiple frames for different seeds to reduce the effect of unexpected tags and also it reduces the time of missing tag detection and identification. RUN identifies 100% missing tags in the presence of unexpected tags where as other protocol only identifies 60% of missing tags.